Protocol for analyzing the biosynthesis and degradation of N-glycan precursors in mammalian cells - Harada, Yoichiro (STAR Protoc, 2021)
N-glycosylation is a fundamental post-translational protein modification in the endoplasmic reticulum of eukaryotic cells. The biosynthetic and catabolic flux of N-glycans in eukaryotic cells has long been analyzed by metabolic labeling using radiolabeled sugars. Here, we introduce a non-radiolabeling protocol for the isolation, structural determination, and quantification of N-glycan precursors, dolichol-linked oligosaccharides, and the related metabolites, including phosphorylated oligosaccharides and nucleotide sugars. Our protocol allows for capturing of the biosynthesis and degradation of N-glycan precursors at steady state. For complete details on the use and execution of this protocol, please refer to Harada et al. (2013), Harada et al. (2020), and Nakajima et al. (2013).